2022
DOI: 10.1210/clinem/dgac542
|View full text |Cite
|
Sign up to set email alerts
|

GIP Affects Hepatic Fat and Brown Adipose Tissue Thermogenesis but Not White Adipose Tissue Transcriptome in Type 1 Diabetes

Abstract: Aims/hypothesis Glucose-dependent insulinotropic polypeptide (GIP) has been proposed to exert insulin-independent effects on lipid and bone metabolism. We investigated the effect of a 6-day s.c. GIP infusion on circulating lipids, white adipose tissue (WAT), brown adipose tissue (BAT), hepatic fat content, inflammatory markers, respiratory exchange ratio (RER), and bone homeostasis in patients with type 1 diabetes. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…The aforementioned 6‐day continuous subcutaneous infusion of GIP in patients with type 1 diabetes resulted in a 12.6% ± 4.2% increase in hepatic lipid content compared with placebo, consistent with earlier proposals of the involvement of GIP in the lipid metabolism 66 . Moreover, levels of endogenous GIP have been linked to various inflammatory processes 91–93 and autonomic disturbances of the cardiovascular system, 94 but no causalities have been established.…”
Section: Therapeutic Effects Of Glp‐1 and Gipsupporting
confidence: 85%
See 3 more Smart Citations
“…The aforementioned 6‐day continuous subcutaneous infusion of GIP in patients with type 1 diabetes resulted in a 12.6% ± 4.2% increase in hepatic lipid content compared with placebo, consistent with earlier proposals of the involvement of GIP in the lipid metabolism 66 . Moreover, levels of endogenous GIP have been linked to various inflammatory processes 91–93 and autonomic disturbances of the cardiovascular system, 94 but no causalities have been established.…”
Section: Therapeutic Effects Of Glp‐1 and Gipsupporting
confidence: 85%
“…Thus, only acute studies of the effects of natural GIP are available, apart from a single study with a 6-day infusion of GIP in patients with type 1 diabetes. 65,66 Recently (May 2023), Novo Nordisk announced termination of the development of a onceweekly GIP receptor agonist (NNC0480-0389) because of a lack of effect on glycaemia and body weight following 34 weeks of treatment with or without concomitant treatment with the GLP-1 receptor agonist semaglutide in patients with type 2 diabetes. 67 By contrast, Eli Lilly and Company presented body weight loss and reduced fasting plasma glucose using a long-acting GIP analogue (LY3537021) for 2 months in both patients with type 2 diabetes and healthy individuals.…”
Section: Therapeutic Effects Of Glp-1 and Gipmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also reported an increase in P1NP during GIP administration which is suggestive of bone anabolic effects of GIP [47 && ]. However, the effect of GIP on bone turnover may be transient as a six-day infusion of GIP only displayed a decrease in CTX at the initiation of the infusion, but not after one or six days compared to placebo in patients with type 1 diabetes [48]. This suggests that GIP should be given pulsatile if it should be used as a target in the treatment of osteoporosis.…”
Section: Glp-1mentioning
confidence: 99%